A novel AIOD-CRISPR system for diagnosis of SARS-CoV-2 - Liu, Changchun (Henry Stewart Talks, 2020)
Background technology of the AIOD-CRISPR diagnostic test, Difference from other CRISPR based tests, Test sensitivity, Development of this diagnostic test for commercial use